Aplikasi Edible Coating Pati Bengkuang (Pachyrhizus Erosus) Dan Kunyit (Curcuma Longa) Untuk Meminimalkan Kerusakan Buah Sawo (Manilkara Zapota) : Edible Coating untuk Mempertahankan Kualitas dan Masa Simpan Buah Sawo - Kennis Rozana; Sarah Firdausia Damayanti (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2025)
Sapodilla fruit is one of the horticultural commodities with high nutritional value but is easily damaged, so it requires post-harvest treatment to extend its shelf life. One effort that can be made is the application of edible coating based on natural ingredients that can maintain fruit quality. This study aims to evaluate the effectiveness of edible coating made from yam starch with the addition of turmeric filtrate on the shelf life and quality of sapodilla fruit. The parameters observed include weight loss, skin colour, flesh colour, texture, aroma, and fruit tastes during storage. The coating method was carried out using a dipping technique in five treatment variations, namely K + (positive control), K- (negative control), F1 (EC + 5% turmeric filtrate), F2 (EC + 10% turmeric filtrate), and F3 (EC + 15% turmeric filtrate). The results showed that the F3 treatment was the most effective in extending the shelf life up to 21 days while maintaining the organoleptic quality of sapodilla fruit. The addition of turmeric filtrate in edible coating has been shown to slow down the rate of damage, so it has the potential as a natural solution to maintain the quality of sapodilla fruit during storage.